UBE2N Regulates Paclitaxel Sensitivity of Ovarian Cancer via Fos/P53 Axis - Zhu, Qiuyuan (Onco Targets Ther, 2020)
BACKGROUND: Chemo-resistance is still considered one of the key factors in the mortality of ovarian cancer. In this work, we found that ubiquitin-conjugating enzyme E2 N (UBE2N) is downregulated in paclitaxel-resistant ovarian cancer cells. It suggests UBE2N to be critical in the regulation of paclitaxel sensitivity in ovarian cancer. MATERIALS AND METHODS: Ovarian cancer cells with stably overexpressed UBE2N were injected into nude mice to assess tumor growth and paclitaxel sensitivity in vivo. The MTT assay was applied to observe the effect of UBE2N expression on paclitaxel sensitivity. A real-time PCR array, specific for human cancer drug resistance, was used to examine the potential downstream target genes of UBE2N. The expression of UBE2N and potential downstream target genes was determined by Western blotting. The analysis of Gene Ontology and protein–protein interactions of these differentially expressed genes (DEGs) was performed using online tools. To evaluate the prognostic value of hub genes expression for ovarian cancer patients treated with paclitaxel, we applied the online survival analysis tool. RESULTS: Overexpressed UBE2N enhanced the paclitaxel sensitivity of ovarian cancer cells in vitro and in vivo. Thirteen upregulated DEGs and 11 downregulated DEGs were identified when we knockdown UBE2N. Meanwhile, 9 hub genes with a high degree of connectivity were selected. Only Fos proto-oncogene, AP-1 transcription factor subunit (Fos), was overexpressed upon decreasing UBE2N levels, indicating a poor outcome for patients treated with paclitaxel. Moreover, reduced UBE2N could increase Fos expression and reduce P53. Furthermore, reversed regulation of Fos and P53 based on UBE2N reduction could reverse paclitaxel sensitivity, respectively. CONCLUSION: Our study suggests that UBE2N could be used as a therapeutic agent for paclitaxel-resistant ovarian cancer through Fos/P53 pathway. Further studies are needed to elucidate the specific mechanism.